Etika dan Budaya Organisasi Berbasis Syariah: Studi Kasus Koperasi Syariah Mitra Iltizam Indonesia - Ikram Kasyful Azhim; Lisa Natalia; Syifa Nur Izzati; Fahala Rizka (Aksioreligia, 2025)
This research aims to comprehensively analyze and deeply investigate the application of Islamic-based business ethics and organizational culture at Koperasi Syariah Mitra Iltizam Indonesia. In the modern Islamic economic landscape and Islamic microfinance institutions, business entities are required not only to orient themselves toward financial profit maximization and capital accumulation but also to ensure spiritual integrity, comprehensive Sharia compliance (kaffah), and equilibrium (tawazun) between worldly and otherworldly orientations. The methodological approach utilized in this study is a qualitative method through an intrinsic case study design, making use of in-depth interviews with cooperative management, participatory observation of the work ecosystem, and analysis of organizational documents and digital platforms. The findings indicate that Koperasi Syariah Mitra Iltizam comprehensively internalizes Sharia ethical principles such as monotheism (tauhid), justice (al-'adl), trustworthiness (ash-shidiq), social responsibility (al-mas’uliyyah al-ijtima’iyyah), and the absolute avoidance of riba, gharar, and maysir practices. This cultural transformation is concretely manifested through policy interventions such as daily Quranic halaqah, the integration of Key Performance Indicator (KPI) systems with spiritual achievements (such as Quranic memorization and worship discipline as a condition for salary disbursement), and the utilization of integrated digital technology to ensure operational transparency that eliminates information asymmetry. Although there are significant cultural challenges regarding initial resistance and the paradigm shift from conventional systems to strict Sharia systems, spiritual leadership within the organization has successfully mitigated these challenges through role modeling and continuous education. Consequently, there has been a drastic increase in Organizational Citizenship Behavior (OCB), intrinsic motivation based on the paradigm of work as worship, improvement in moral character, and a surge in the functional performance of the members. This study provides a theoretical contribution to the literature on Islamic organizational behavior and offers a practical model that can be replicated by other Islamic microfinance institutions in striving for an ethical, transparent, just, and blessed business ecosystem.